Yield and fruit quality of bagging peach cultivar Coral - Telles, Charles Allan (2004)
The effect of different bags on peach fruit quality and fruit flies damage control was studied. Theexperiment was carried out in a Coral peach orchard with organic management at Canguiri Experimental Farm of UFPR, Pinhais, PR. The treatments were: bags of newspaper, bags of kraft, bags of tissue paper and control (without bagging). The experimental design was randomized blocks with five replicates, each one with two plants. Twenty fruits in each branch were selected per treatment. All fruits protected with paper-bags presented great uniformityand absence of fruit-fly injuries. The best bag was treatment tissue paper that induced highest percentage of red color (39,2%) and higher soluble solids content (10,14oBrix) in the fruits.